PENGARUH JUMLAH PELAT KUNINGAN PADA CATALYTIC CONVERTER TERHADAP EMISI GAS BUANG KARBON MONOKSIDA PADA MOTOR BENSIN 100 CC: ANALYSIS OF THE EFFECT OF THE NUMBER AND THICKNESS OF PLATES BRASS ON CATALYTIC CONVERTER ON EXHAUST GAS EMISSIONS 100 CC GASOLINE MOTORCYCLE - Firdaus, Ahmad Hanif; Celvin Yoga P, Bryan (Jurnal Teknik Mesin, 2024)
Exhaust gas emissions are pollutants that pollute the air resulting from vehicle exhaust gas. The aim of this research is to determine the results of the influence of the number and thickness of plates on exhaust emissions from 100 cc motorbikes, and to provide an alternative to reduce exhaust emissions using a catalytic converter made from brass at a cheaper price. To verify its performance, experimental research methods were used in this thesis research. The research results showed that the number and thickness of brass plates had an effect on reducing CO and HC emissions. For example, using a number of plates of 5 and a thickness of 1 mm produces the lowest CO gas, namely 0.33 g/km, at an engine speed of 3000 rpm, while the HC gas produced is 73 ppm at 3000 rpm. This can happen because the more and thicker the plates are used. be a factor in reducing exhaust emissions